Quantum periods for certain four-dimensional Fano manifolds - Coates, Tom; Galkin, Sergey; Kasprzyk, Alexander M.; Strangeway, Andrew (Taylor & Francis, 2018)
We collect a list of known four-dimensional Fano manifolds and compute their quantum periods. This list includes all four-dimensional Fano manifolds of index greater than one, all four-dimensional toric Fano manifolds, all four-dimensional products of lower-dimensional Fano manifolds, and certain complete intersections in projective bundles.